Kondisi Kehidupan Pedesaan Terhadap Tantangan Pembinaan Muallaf (Studi Kasus Interaksi Masyarakat Dusun Parasung Desa Paramasan Bawah): Case Study of Society Interaction in Parasung, Paramasan Bawah, Banjar, South Kalimantan - Nuraini, Dewi Fauziah (Jurnal Penelitian Ilmiah INTAJ, 2025)
This research aims to find out the challenges of Muallaf development based on the background and conditions of the research location. The location of this research is Parasung Hamlet, Paramasan Bawah Village, Paramasan Subdistrict, Banjar Regency, South Kalimantan. This is a remote area, far from the city center, so the hamlet and village where this research is located are rarely touched by people outside their area. This research uses descriptive qualitative method. The data presented is based on the results of field research with data collection techniques including observation, unstructured interviews and documentation, then the data obtained and collected are then processed and presented along with their interpretations. The results of this study indicate that all aspects of human life have their own roles to play in the development and management of muallaf. The many challenges in the development of Muallaf need to be dealt with on an ongoing basis and it is very necessary to be a concern among fellow human beings and especially by authorized institutions in order to create equality in the welfare of society.